A storm in Sāmoa: an environmental microhistory. Issue 1 (2nd January 2017) - Rosenthal, Gregory
Abstract: Environmental historians generally consider longue durée processes, such as geological, biological, and evolutionary changes, as useful bases for undergirding narratives of the human past. Yet singular, momentary events offer just as much insight into history's big questions of empire, capitalism, globalization, and environmental change. The story of a tropical cyclone – as it blows in from stage left, wreaks havoc at center stage, and then exits stage right – calls for a different kind of storytelling, more fast-paced, yet no less attuned to the interplay among human and non-human forces. In this essay, I look at 24 h within the story of a tropical cyclone that hit Apia, Sāmoa, on March 16, 1889, to demonstrate just how many stories can be told within the environmental microhistory of a singular event. I employ several unorthodox narrative devices – blending real dialog with a fictionalized internal monolog; jumping back and forth through time and space; and, pitting two odd, yet very real, characters against one another: a Japanese cabin steward on an American Naval ship, and an exiled Sāmoan leader on a Micronesian atoll – to play with the possibilities of environmental microhistory as a new form of historical storytelling.